Mindfulness Affects the Level of Psychological Distress in Patients With Lung Cancer via Illness Perception and Perceived Stress: A Cross-Sectional Survey Study - Tian, Xu; Tang, Ling; Yi, Li-Juan; Qin, Xiao-Pei; Chen, Gui-Hua; Jiménez-Herrera, Maria F. (Frontiers in Psychology, 2022)
Purpose: The aims of the study were firstly to investigate the association between illness perception and psychological distress and secondly determine whether mindfulness affect psychological distress via illness perception and perceived stress in lung cancer patients. Method: Among 300 lung cancer patients participated in this cross-sectional study, 295 patients made valid responses to Distress Thermometer (DT), Five Facet Mindfulness Questionnaire (FFMQ), Brief Illness Perception Questionnaire (B-IPQ), and Perceived Stress Scale (PSS) between January and July 2021. The possible pathways of mindfulness affecting psychological distress were analyzed based on the structural equation modelling analysis. Results: A total of 24.4% lung cancer patients had DT >4. Illness perception (β=0.17, p=0.002) and perceived stress (β=0.23, p<0.001) had a direct effect on psychological distress. Mindfulness had a direct effect on illness perception (β=-0.16, p=0.006), and mindfulness indirectly influenced psychological distress (β=-0.04, p=0.009) through affecting illness perception alone or simultaneously affecting both illness perception and perceived stress in lung cancer patients. Conclusions: Lung cancer suffered from varying levels of psychological distress. Mindfulness may alleviate psychological distress by reducing the level of illness perception and perceived stress. We suggest developing comprehensive factor model to clarify potential mechanisms of mindfulness on psychological distress due to very low effect of mindfulness on psychological distress via illness perception and perceived stress.